The CIA's greatest covert operation inside the daring mission to recover a nuclear-armed Soviet sub - Sharp, David H. (University Press of Kansas, 2012)
Recounts Project AZORIAN, the clandestine Cold War efforts of the CIA, under the guise of an undersea mining operation, to recover the sunken Soviet ballistic-missile submarine K-129 from the depths of the Pacific Ocean